2015
DOI: 10.1007/8904_2015_487
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Refsum Disease: Influence of Dietary Treatment on Plasma Phytanic Acid Levels

Abstract: Infantile Refsum disease (IRD) is one of the less severe of Zellweger spectrum disorders (ZSDs), a group of peroxisomal biogenesis disorders resulting from a generalized peroxisomal function impairment. Increased plasma levels of very long chain fatty acids (VLCFA) and phytanic acid are biomarkers used in IRD diagnosis. Furthermore, an increased plasma level of phytanic acid is known to be associated with neurologic damage. Treatment of IRD is symptomatic and multidisciplinary.The authors report a 3-year-old c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Case management of infantile Refsum disease (IRD) is multidisciplinary, but treatment is still only symptomatic (Sa) [ 22 ]. Reports on the impact of treatment on disease progression are limited, probably due to the small number of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case management of infantile Refsum disease (IRD) is multidisciplinary, but treatment is still only symptomatic (Sa) [ 22 ]. Reports on the impact of treatment on disease progression are limited, probably due to the small number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, some research [Sa, Moser] has shown that dietary changes lead to specific biochemical effects. Further studies are needed to evaluate the impact of a low-phytanic-acid diet in the recommended management of patients with IRD [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Natomiast kwas fitanowy pochodzi wyłącznie ze źródeł egzogennych, stąd zastosowanie diety eliminacyjnej powoduje normalizację poziomu tego biomarkera w surowicy i co najważniejsze koresponduje z poprawą funkcji neurologicznych [57,58].…”
Section: Choroby Pbdunclassified
“…With reduction of phytanic acid levels developmental progression of neurological signs can be slowed or prevented. Monitoring of the treatment effect is possible in the short term by the quantification of serum phytanic acid [4]. Besides the general clinical development, objective and easy-to-apply methods for the evaluation of long-term treatment effects are not established.…”
Section: Introductionmentioning
confidence: 99%